Janus hydrogel adhesive as well as preparation method and application thereof

A novel method for preparing Janus hydrogel adhesives with asymmetric adhesion using in-situ gelation and metal coordination addresses the limitations of existing methods, resulting in a hydrogel with controlled adhesion and mechanical stability for tissue repair applications.

CN119144255APending Publication Date: 2024-12-17ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY

Patent Information

Application Number
CN202411091615.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing methods for preparing Janus hydrogel adhesives with asymmetric adhesion properties are complex, require expensive equipment, affect mechanical properties, or result in undesired adhesion to non-target surfaces, limiting their clinical application in tissue repair.

Method used

A method involving in-situ gelation/coordination at the interface using monomers with coordination groups, natural polymers, and metal plates to create a Janus hydrogel adhesive with asymmetric adhesion, where one side is non-adhesive due to metal ion coordination and the other side is adhesive, achieved through thermal polymerization.

Benefits of technology

The method produces a hydrogel adhesive with good mechanical properties and tissue adhesion, allowing for controlled asymmetric adhesion without affecting the adhesive layer, is easy to manufacture, and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144255A_ABST
    Figure CN119144255A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrogel adhesives, and relates to a Janus hydrogel adhesive and a preparation method thereof. The preparation method comprises the following steps: dissolving a monomer with a coordination group, a surfactant, a cross-linking agent, a thermal initiator, a pH regulator and a natural polymer with a strong adhesion site in water, and carrying out one-step thermal initiation polymerization in a manner of covering a hydrogel pre-solution with a specific metal plate to prepare the Janus hydrogel adhesive. An in-situ cross-linking reaction / coordination effect occurs at a metal interface, so that one side of a covering metal plate in the hydrogel achieves an anti-adhesion effect; through the synergistic effect of bonding sites such as a coordination group, a hydroxyl group and an amino group, the strong adhesion effect of one side, which is not covered with a metal plate, in hydrogel is achieved, so that the Janus hydrogel adhesive with asymmetric adhesion is obtained. The method is suitable for preparing asymmetric adhesive gel and postoperative anti-adhesion materials, is used in the fields of intelligent sensors, flexible electronic devices, ultrasonic couplants and the like, is simple and convenient in preparation process, low in cost and easy for large-scale production, and has potential application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogel adhesives, and in particular to a Janus hydrogel adhesive and a preparation method and application thereof. Background Art

[0002] Hydrogel adhesives have the advantages of good biocompatibility, easy modification, and high water content. They play a vital role in the fields of tissue adhesives, wound dressings, hemostatic materials, and drug-carrying materials. However, most of the reported hydrogel adhesives are designed for double-sided adhesion. This indiscriminate adhesion property will cause the material to not only adhere to the wound when used, but also to adhere to the tissue on the other side. This adhesion is very detrimental to wound recovery and the normal activities of the organism, thus severely limiting its clinical application in tissue repair. Therefore, in order to solve this problem, it is of great clinical significance to design and construct a Janus hydrogel adhesive with asymmetric adhesion properties on both sides.

[0003] Currently, the known preparation methods of Janus hydrogel adhesives with asymmetric adhesion properties are relatively limited. Commonly used methods include immersion method (Nano Today, 2024, DOI:10.1016 / j.nantod.2023.102105), coating method (Advanced Functional Materials, 2024, DOI: 10.1002 / adfm.202401030), step-by-step synthesis method (Advanced Science, 2023, DOI: 10.1002 / advs.202301427), electrostatic field method (CN116813945A), mold casting method (Nanoscale, 2014, DOI: 10.1039 / c3nr05865d), etc. Among them, the immersion method requires secondary treatment of the solution, and the gel is prone to swelling, resulting in deterioration of its mechanical properties; the coating method is to use a high concentration of metal ion solution to coat one side of the hydrogel, which reduces its adhesion performance, but the metal ions easily diffuse to the uncoated side (International Journal of Biological Macromolecules, 2021, DOI: 10.1016 / j.ijbiomac.2021.05.203; Bioactive Materials, 2022, DOI: 10.1016 / j.bioactmat.2022.05.010), affecting its adhesion performance; the step-by-step polymerization method requires step-by-step polymerization, which easily leads to the two layers of gel not being firmly combined and stratified; the electrostatic field method and the mold casting method often require expensive manufacturing equipment and complex preparation processes. Therefore, based on the above analysis, it is necessary to provide a simple, efficient and scalable Janus adhesive gel preparation method to overcome the shortcomings of the prior art. The purpose of the present invention is to provide an economical and practical preparation method that can achieve reliable adhesion performance in different environments, thereby meeting a wide range of application needs. Summary of the invention

[0004] In order to solve the shortcomings and deficiencies of the prior art, the present invention provides a method for preparing a novel Janus hydrogel adhesive. The present invention prepares a Janus hydrogel adhesive with asymmetric adhesion on both sides based on in-situ gelation / coordination of the hydrogel at the interface, and the prepared Janus hydrogel adhesive has good mechanical properties and tissue adhesion properties.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a Janus hydrogel adhesive comprises the following steps: (1) Dissolving a monomer with a coordination group, a cross-linking agent, a thermal initiator, a pH adjuster, and a natural polymer in water and stirring the mixture to obtain a hydrogel prepolymer solution; (2) pouring the hydrogel prepolymer obtained in step (1) into a molding mold, and covering the mold with a metal plate to keep it close to the hydrogel prepolymer; (3) The mold of step (2) is placed in an oven to initiate thermal polymerization, thereby obtaining the Janus hydrogel adhesive.

[0006] Furthermore, the monomer with a coordinating group in step (1) may be one or a mixture of acrylamide, acrylhydrazide, acrylic acid, vinylimidazole and sodium acrylate.

[0007] Furthermore, the monomer with coordination groups described in step (1) accounts for 8-40wt% of the mass of the hydrogel prepolymer solution; the cross-linking agent accounts for 0.01-0.5wt% of the mass of the hydrogel prepolymer solution; the thermal initiator accounts for 0.01-0.3wt% of the mass of the hydrogel prepolymer solution; the pH regulator accounts for 0.01-0.5wt% of the mass of the hydrogel prepolymer solution; and the natural polymer accounts for 0.5-4wt% of the mass of the hydrogel prepolymer solution.

[0008] Furthermore, the pH adjuster in step (1) is one or more of glacial acetic acid, citric acid, hydrochloric acid, and sulfuric acid.

[0009] Furthermore, the pH value of the hydrogel prepolymer solution in step (1) is 1 to 6.

[0010] Furthermore, the natural polymer described in step (1) is one or more of chitosan, carboxymethyl chitosan, sodium alginate, gelatin, hyaluronic acid, starch, sodium carboxymethyl cellulose, and polyethyleneimine.

[0011] Furthermore, the cross-linking agent in step (1) may be one or more of N,N'-methylenebisacrylamide and polyethylene glycol diacrylate.

[0012] Furthermore, the thermal initiator in step (1) is one or more of ammonium persulfate, ammonium hydrogen persulfate, potassium persulfate and sodium persulfate.

[0013] Furthermore, the metal plate in step (1) is one of an aluminum plate, a copper plate, a zinc plate, an iron plate, a stainless steel plate and an aluminum alloy plate, preferably an aluminum plate.

[0014] Furthermore, the temperature of the oven in step (1) is 25 to 100° C., and the time of thermally initiated polymerization is 1 to 10 hours.

[0015] The present invention also provides a Janus hydrogel adhesive prepared by the above preparation method.

[0016] The Janus hydrogel adhesive of the invention is used in preparing an asymmetric hydrogel adhesive or a postoperative anti-adhesion material, an intelligent sensor, a flexible electronic device and an ultrasonic coupling agent.

[0017] The present invention is based on monomers with coordination groups and natural polymers, such as acrylhydrazide and chitosan, and adopts a new method of covering metal plates to construct a Janus hydrogel adhesive with asymmetric adhesion on both sides. Among them, polyacrylhydrazide has a large number of metal coordination groups and adhesion groups in its structure; the hydroxyl groups in chitosan can form hydrogen bonds and electrostatic interactions with the surfaces of various substrates, etc., giving the hydrogel excellent adhesion properties. During the thermal polymerization process, on the side covered with the metal plate, by controlling the pH value of the hydrogel and the material of the metal plate, the metal ions generated by the metal plate at the interface can coordinate with the coordination groups and the amino groups in the chitosan, thereby reducing the non-covalent adhesion between it and the substrate, and realizing the controllable construction of the Janus hydrogel adhesive with asymmetric adhesion on both sides. The prepared hydrogel has good mechanical properties, tissue adhesion and acoustic conductivity.

[0018] Compared with the prior art, the present invention has the following advantages: (1) The Janus hydrogel adhesive prepared by the present invention has one side (i.e., the non-adhesive layer) formed by in-situ gelation / coordination at the interface, and a large number of adhesive groups form coordination with metal ions, resulting in loss of adhesive properties; while the other side (i.e., the adhesive layer) of the hydrogel can retain the adhesive groups to produce a strong bond, thereby achieving an asymmetric adhesion effect.

[0019] (2) The Janus hydrogel adhesive prepared by the present invention is a non-adhesive layer obtained by in-situ metal coordination, wherein the metal ions will not diffuse into the adhesive layer, and thus will not affect the adhesive properties of the adhesive layer; (3) The Janus hydrogel adhesive prepared by the present invention does not require secondary immersion or secondary surface treatment, can be prepared in one step, will not affect the mechanical properties of the hydrogel, and is easy to manufacture on a large scale; (4) The Janus hydrogel adhesive prepared by the present invention uses materials with good biocompatibility and has great application and promotion value in the fields of tissue adhesion and ultrasonic conduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 This is a physical picture of the Janus hydrogel adhesive prepared in Example 3.

[0022] Figure 2 3 is a diagram of the formation mechanism of the Janus hydrogel adhesive prepared in Example 3.

[0023] Figure 3 The following are actual pictures showing the adhesion of the Janus hydrogel adhesive prepared in Example 3 to different substrates.

[0024] Figure 4 3 is an adhesion force-displacement curve of the Janus hydrogel adhesive shear test prepared in Example 3.

[0025] Figure 5 This is the X-ray photoelectron spectrum of the upper and lower surfaces of the Janus hydrogel adhesive prepared in Example 3. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely exemplary and do not constitute any limitation to the scope of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0027] Sources of the raw materials used in the following examples are as follows: acrylamide, acrylhydrazide, acrylic acid, vinylimidazole, sodium acrylate, chitosan, carboxymethyl chitosan, sodium alginate, gelatin, hyaluronic acid, starch, sodium carboxymethyl cellulose, polyethyleneimine, ammonium persulfate (APS), ammonium hydrogen persulfate, potassium persulfate, sodium persulfate, glacial acetic acid, citric acid, hydrochloric acid, sulfuric acid, N,N'-methylenebisacrylamide (MBA) and polyethylene glycol diacrylate (PEGDA) were all purchased from Shanghai MacLean Biotechnology Co., Ltd.

[0028] Example 1 A method for preparing a Janus hydrogel adhesive comprises the following steps: (1) Weigh 1.2 g of acryloyl hydrazide, 0.15 g of sodium alginate, 0.05 g of hyaluronic acid, 12 mg of thermal initiator ammonium persulfate, and 20 mg of cross-linking agent MBA, dissolve in deionized water, adjust the pH to 4 with sulfuric acid, and prepare a 10 mL solution. Stir evenly at room temperature; (2) Pour the mixed solution obtained in step (1) into a PTFE mold, cover it with a copper plate, and place it in an oven for thermal initiation at 54°C for 6 hours. Through a polymerization and cross-linking process, the precursor mixture is cured in a specific molding mold. After curing, the mold is cooled to ambient temperature to ensure the stability of the gel structure. Subsequently, the metal cover on the mold is carefully removed to avoid any damage to the gel. Using a professional chrome-plated tool, the gel is precisely removed from the mold to obtain an adhesive hydrogel with Janus properties.

[0029] Example 2 A method for preparing a Janus hydrogel adhesive comprises the following steps: (1) Weigh 1.3 g acrylic acid, 0.1 g polyethyleneimine, 0.1 g sodium carboxymethyl cellulose, 0.05 g gelatin, 10 mg thermal initiator potassium persulfate, and 25 mg cross-linking agent PEGDA, dissolve in deionized water, adjust pH to 5 with hydrochloric acid, and prepare a 10 mL solution. Stir evenly at room temperature. (2) Pour the mixed solution obtained in step (1) into a PTFE mold, cover it with a zinc plate, and place it in an oven for thermal initiation at 60°C for 5 hours. Through a polymerization and cross-linking process, the precursor mixture is cured in a specific molding mold. After curing, the mold is cooled to ambient temperature to ensure the stability of the gel structure. Subsequently, the metal cover on the mold is carefully removed to avoid any damage to the gel. Using a professional chrome-plated tool, the gel is precisely removed from the mold to obtain an adhesive hydrogel with Janus properties.

[0030] Example 3 A method for preparing a Janus-type adhesive hydrogel comprises the following steps: (1) Weigh 1 g acrylamide, 0.1 g chitosan, 10 mg thermal initiator APS, and 24 mg crosslinker MBA, dissolve in deionized water, adjust the pH to 5.5 with glacial acetic acid, and prepare 10 mL solution. Stir evenly at room temperature. (2) Pour the mixed solution obtained in step (1) into a PTFE mold, cover it with an aluminum plate, and place it in an oven for thermal initiation at 75°C for 3 hours. Through a polymerization and cross-linking process, the precursor mixture is cured in a specific molding mold. After curing, the mold is cooled to ambient temperature to ensure the stability of the gel structure. Subsequently, the metal cover on the mold is carefully removed to avoid any damage to the gel. Using a professional chrome-plated tool, the gel is precisely removed from the mold to obtain an adhesive hydrogel with Janus properties.

[0031] The Janus hydrogel adhesive prepared in this embodiment is as follows Figure 1 Show.

[0032] The principle preparation diagram of the Janus hydrogel adhesive prepared in this embodiment is as follows Figure 2 Show.

[0033] The adhesive layer of the Janus hydrogel adhesive prepared in this example was placed in contact with the surfaces of different substrates, and the non-adhesive layer was adhered to the finger using double-sided tape, and a little pressure was applied to make the gel fully adhere to the substrate. Figure 3 As shown, it can be seen that the Janus-type adhesive hydrogel of the present invention can directly adhere to the surfaces of different substrates, including pigskin, glass, iron, plastic, PTFE and rubber.

[0034] Figure 4 3 is an adhesion force-displacement curve of the Janus hydrogel adhesive shear test prepared in Example 3. Figure 5 The following is an X-ray photoelectron spectrum of the upper and lower surfaces of the Janus hydrogel adhesive prepared in Example 3. Figure 5 It can be seen that the metal ions do not diffuse into the adhesive layer and thus do not affect the adhesive properties of the adhesive layer.

[0035] Example 4 A method for preparing a Janus hydrogel adhesive comprises the following steps: (1) Weigh 1.5 g vinylimidazole, 0.15 g carboxymethyl chitosan, 60 mg thermal initiator sodium persulfate, and 20 mg cross-linking agent PEGDA, dissolve in deionized water, adjust the pH to 6 with glacial acetic acid, and prepare a 10 mL solution. Stir evenly at room temperature; (2) Pour the mixed solution obtained in step (1) into a PTFE mold, cover it with an iron plate, and place it in an oven for thermal initiation at 54°C for 6 hours. Through a polymerization and cross-linking process, the precursor mixture is cured in a specific molding mold. After curing, the mold is cooled to ambient temperature to ensure the stability of the gel structure. Subsequently, the metal cover on the mold is carefully removed to avoid any damage to the gel. Using a professional chrome-plated tool, the gel is precisely removed from the mold to obtain an adhesive hydrogel with Janus properties.

[0036] Example 5 A method for preparing a Janus hydrogel adhesive comprises the following steps: (1) Weigh 1.2 g sodium acrylate, 0.15 g carboxymethyl chitosan, 30 mg thermal initiator potassium persulfate, and 24 mg crosslinker MBA, dissolve in deionized water, adjust pH to 6 with glacial acetic acid, and prepare 10 mL solution. Stir evenly at room temperature. (2) Pour the mixed solution obtained in step (1) into a PTFE mold, cover it with a stainless steel plate, and place it in an oven for thermal initiation at 54°C for 6 hours. Through a polymerization and cross-linking process, the precursor mixture is cured in a specific molding mold. After curing, the mold is cooled to ambient temperature to ensure the stability of the gel structure. Subsequently, the metal cover on the mold is carefully removed to avoid any damage to the gel. Using a professional chrome-plated tool, the gel is precisely removed from the mold to obtain an adhesive hydrogel with Janus properties.

[0037] Example 6 A method for preparing a Janus-type adhesive hydrogel comprises the following steps: (1) Weigh 1.5 g acrylamide, 0.1 g chitosan, 10 mg thermal initiator APS, and 24 mg crosslinker MBA, dissolve in deionized water, adjust the pH to 5 with glacial acetic acid, and prepare a 10 mL solution. Stir evenly at room temperature. (2) Pour the mixed solution obtained in step (1) into a PTFE mold, cover it with an aluminum alloy plate, and place it in an oven at 60°C for 5 h to cure the precursor mixture in a specific molding mold through a polymerization cross-linking process. After curing, cool the mold to ambient temperature to ensure the stability of the gel structure. Subsequently, carefully remove the metal cover on the mold to avoid any damage to the gel. Use a professional chrome-plated tool to accurately remove the gel from the mold to obtain an adhesive hydrogel with Janus properties.

[0038] Comparative Example 1 According to the method of Example 1, the components are the same as those of Example 1, and the operation is different from that of Example 1 in that the copper plate is not covered for polymerization. The hydrogel adhesive obtained by polymerization and cross-linking does not show an asymmetric adhesion effect on both sides, as shown in Table 2.

[0039] Comparative Example 2 According to the method of Example 2, the components are the same as those of Example 2, and the operation is different from that of Example 2 in that the zinc plate is not covered for polymerization. The hydrogel adhesive obtained by polymerization and cross-linking does not show an asymmetric adhesion effect on both sides, as shown in Table 2.

[0040] Comparative Example 3 According to the method of Example 3, the components are the same as those of Example 3. The operation is different from that of Example 3 in that the aluminum plate is not covered for polymerization. The hydrogel adhesive obtained by polymerization and cross-linking does not show an asymmetric adhesion effect on both sides, as shown in Table 2.

[0041] Comparative Example 4 According to the method of Example 4, the components are the same as those of Example 4. The operation is different from that of Example 4 in that the iron plate is not covered for polymerization. The hydrogel adhesive obtained by polymerization and cross-linking does not show an asymmetric adhesion effect on both sides, as shown in Table 2.

[0042] Comparative Example 5 According to the method of Example 5, the components are the same as those of Example 5, and the operation is different from that of Example 5 in that the stainless steel plate is not covered for polymerization. The hydrogel adhesive obtained by polymerization and cross-linking does not show the asymmetric adhesion effect on both sides.

[0043] Comparative Example 6 According to the method of Example 6, the components are the same as those of Example 6. The operation is different from that of Example 6 in that the aluminum alloy plate is not covered for polymerization. The hydrogel adhesive obtained by polymerization and cross-linking does not show an asymmetric adhesion effect on both sides, as shown in Table 2.

[0044] The Janus hydrogel adhesive prepared by the present invention was cut into a size of 20 mm×20 mm, the anti-adhesive layer was adhered to the substrate to be tested with a double-sided tape, the adhesive layer was adhered to pig skin, and then pressed with a 500 g weight for 2 minutes. The adhesion shear test was performed using a UTM2202 universal testing machine of Shenzhen Sansi Zongheng Technology Co., Ltd. The measurement conditions of the adhesion shear test were: the tensile speed was set to 50 mm / min and the temperature was room temperature.

[0045] Table 1 Adhesion strength of the Janus hydrogel adhesives of Examples 1 to 6 on the adhesive side and the non-adhesive side to pig skin Table 2 Adhesion strength of the top and bottom of the Janus hydrogel adhesive of Comparative Examples 1 to 6 to pig skin The hydrogels prepared in Comparative Examples 1 to 6 are respectively compared with Examples 1 to 6. The hydrogels prepared in Comparative Examples 1 to 6 do not show asymmetric adhesion effect. It should be noted that high-valent metal ions form charged ions in the solution, which can repel the adhesive material with opposite charge, thereby reducing the adhesion force; they can also react chemically with the surface of the material to change its surface chemical composition and structure. 3+ ) Due to its higher charge density, it exhibits a higher coordination number, which enables it to form stable coordination complexes with more ligand molecules. This high charge density gives the trivalent aluminum ion a stronger electrostatic attraction with the ligand, thereby enhancing the binding strength of the coordination bond. This enhanced binding strength not only improves the thermodynamic stability of the coordination compound, but also expands its application functionality in chemistry, materials science, and biotechnology. Therefore, when forming coordination compounds, trivalent aluminum ions exhibit higher chemical selectivity and structural stability than divalent metal ions, which is particularly important in the preparation of coordination compounds with specific properties, and can also more effectively consume adhesion groups. This also shows that covering the metal plate is the key to the successful preparation of Janus hydrogel adhesives.

[0046] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a Janus hydrogel adhesive, characterized in that: The steps include: (1) Dissolving a monomer with a coordination group, a cross-linking agent, a thermal initiator, a pH adjuster, and a natural polymer in water and stirring the mixture to obtain a hydrogel prepolymer solution; (2) pouring the hydrogel prepolymer obtained in step (1) into a mold, and covering the mold with a metal plate so that it is close to the hydrogel prepolymer; (3) The mold of step (2) is placed in an oven and subjected to thermal polymerization at a certain temperature to obtain the Janus hydrogel adhesive.

2. The method for preparing the Janus hydrogel adhesive according to claim 1, characterized in that: The monomer with a coordination group in step (1) is one or more of acrylhydrazide, acrylic acid, vinylimidazole and vinylpyrrolidone.

3. The method for preparing the Janus hydrogel adhesive according to claim 1, characterized in that: In the step (1), the monomer with coordination groups accounts for 8-40wt% of the mass of the hydrogel prepolymer solution; the cross-linking agent accounts for 0.01-0.5wt% of the mass of the hydrogel prepolymer solution; the thermal initiator accounts for 0.01-0.3wt% of the mass of the hydrogel prepolymer solution; the pH regulator accounts for 0.01-0.5wt% of the mass of the hydrogel prepolymer solution; and the natural polymer accounts for 0.5-4wt% of the mass of the hydrogel prepolymer solution.

4. The method for preparing the Janus hydrogel adhesive according to claim 1, characterized in that: The pH regulator in step (1) is one or more of glacial acetic acid, citric acid, hydrochloric acid and sulfuric acid, and the pH value of the hydrogel prepolymer solution is 1-6.

5. The method for preparing the Janus hydrogel adhesive according to claim 1, characterized in that: The natural polymer in step (1) is one or more of chitosan, carboxymethyl chitosan, sodium alginate, gelatin, hyaluronic acid, starch, sodium carboxymethyl carboxymethyl cellulose, and polyethyleneimine.

6. The method for preparing the Janus hydrogel adhesive according to claim 1, characterized in that: The cross-linking agent in step (1) is one or more of N,N'-methylenebisacrylamide and polyethylene glycol diacrylate.

7. The method for preparing the Janus hydrogel adhesive according to claim 1, characterized in that: The thermal initiator in step (1) is one or more of ammonium persulfate, ammonium hydrogen persulfate, potassium persulfate and sodium persulfate.

8. The method for preparing the Janus hydrogel adhesive according to claim 1, characterized in that: In the step (2), the metal plate is one of an aluminum plate, a copper plate, a zinc plate, an iron plate, a stainless steel plate and an aluminum alloy plate.

9. The method for preparing the Janus hydrogel adhesive according to claim 1, characterized in that: In the step (1), the temperature of the oven is 25 to 100° C., and the time of thermally initiated polymerization is 1 to 10 hours.

10. A Janus hydrogel adhesive, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing Janus asymmetric wet adhesion hydrogel based on electrostatic field

    CN116813945A

Cited By

  • Preparation method and application of nanosheet adhesive capable of quickly adhering hydrogel

    CN120137590A